Composite positive electrode material, solid-state electrode plate, solid-state battery and energy storage device

By introducing composite positive electrode material structures, including core and polymer conductive fiber layers, the problem of reduced ionic conductivity and electronic conductivity in solid-state batteries is solved, capacity performance and cycling performance are improved, and energy storage efficiency and service life of energy storage devices are enhanced.

CN119674032APending Publication Date: 2025-03-21XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411918217.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Because solid-state batteries use solid-state electrolytes to replace liquid electrolytes, they can easily lead to a decrease in ionic conductivity and electron conductivity, and the structural strength of the positive electrode material is insufficient, which affects capacity performance and cycling performance.

Method used

Composite positive electrode materials are used, including cores and polymer conductive fiber layers, which contain positive electrode active materials, solid electrolytes and one-dimensional conductive fibers to form a closely connected conductive network, and the polymer conductive fiber layer is wound with one-dimensional conductive fibers to form a conductive network to improve structural strength and dynamic performance.

Benefits of technology

It improves the capacity and circulation performance of solid-state batteries, and enhances the energy storage efficiency and service life of energy storage devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674032A_ABST
    Figure CN119674032A_ABST
Patent Text Reader

Abstract

The invention provides a composite positive electrode material, a solid-state electrode plate, a solid-state battery and an energy storage device, the composite positive electrode material comprises an inner core and a polymer conductive fiber layer, and the polymer conductive fiber layer coats at least one part of the surface of the inner core; the inner core comprises a positive electrode active material, a solid electrolyte and one-dimensional conductive fibers, and the one-dimensional conductive fibers are distributed between the positive electrode active material and the solid electrolyte; the polymer conductive fiber layer comprises polymer conductive fibers, and at least part of the polymer conductive fibers and the one-dimensional conductive fibers are mutually wound to form a conductive network.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage technology, and in particular to a composite positive electrode material, a solid-state electrode sheet, a solid-state battery and an energy storage device. Background Art

[0002] Solid-state batteries use solid electrolytes instead of traditional organic liquid electrolytes, which can improve the safety and cycle stability of batteries and are expected to be used in the field of large-scale energy storage.

[0003] However, since solid-state batteries use solid electrolytes instead of liquid electrolytes, the ionic conductivity and electronic conductivity of solid-state batteries are easily reduced. In addition, the structural strength of the positive electrode materials in solid-state batteries still needs to be improved, which affects the capacity performance and cycle performance of solid-state batteries. Summary of the invention

[0004] In order to solve the above technical problems, the present application discloses a composite positive electrode material, a solid-state electrode sheet, a solid-state battery and an energy storage device to improve the capacity performance and cycle performance of the solid-state battery.

[0005] In the first aspect, the present application provides a composite positive electrode material, comprising a core and a polymer conductive fiber layer, wherein the polymer conductive fiber layer is coated on at least a portion of the surface of the core; the core comprises a positive electrode active material, a solid electrolyte and one-dimensional conductive fibers, wherein the one-dimensional conductive fibers are distributed between the positive electrode active material and the solid electrolyte; the polymer conductive fiber layer comprises polymer conductive fibers, and at least part of the polymer conductive fibers are entangled with the one-dimensional conductive fibers to form a conductive network.

[0006] In some embodiments of the present application, the mass percentage of the positive electrode active material in the inner core is a, 85%≤a≤90%, the mass percentage of the solid electrolyte in the inner core is b, 5%≤b≤10%, and the mass percentage of the one-dimensional conductive fiber in the inner core is c, 1%≤c≤3%.

[0007] In some embodiments of the present application, the average length of the one-dimensional conductive fibers is L, 3 μm≤L≤5 μm.

[0008] In some embodiments of the present application, the thickness of the polymer conductive fiber layer is H, 2 μm≤H≤5 μm.

[0009] In some embodiments of the present application, the Dv50 of the composite positive electrode material is 8 μm to 10 μm.

[0010] In some embodiments of the present application, the one-dimensional conductive fibers extend outward from the inner core to the outer surface of the polymer conductive fiber layer.

[0011] In some embodiments of the present application, the one-dimensional conductive fiber includes at least one of carbon conductive fiber and metal conductive fiber.

[0012] In some embodiments of the present application, the polymer in the polymer conductive fiber includes at least one of polyaniline, polypyrrole and polythiophene.

[0013] In some embodiments of the present application, the inner core further includes a binder, and the mass percentage of the binder in the inner core is d, 1%≤d≤3%.

[0014] In a second aspect, the present application provides a solid electrode sheet, comprising a current collector, at least one side of the current collector having a positive electrode material layer, and the positive electrode material layer comprises the composite positive electrode material described in the first aspect.

[0015] In some embodiments of the present application, the solid electrode sheet further includes a solid electrolyte layer, and the solid electrolyte layer is located on a side of the positive electrode material layer facing away from the current collector.

[0016] In a third aspect, the present application provides a solid-state battery, comprising the solid-state electrode sheet described in the first aspect.

[0017] In a fourth aspect, the present application provides an energy storage device, comprising a housing and at least one solid-state battery as described in the third aspect, wherein the solid-state battery is accommodated in the housing.

[0018] In a fifth aspect, the present application provides an electrical device, comprising the energy storage device described in the fourth aspect, wherein the energy storage device supplies power to the electrical device.

[0019] Compared with the prior art, this application has at least the following beneficial effects:

[0020] The present application provides a composite positive electrode material, a solid electrode sheet, a solid-state battery and an energy storage device, wherein the composite positive electrode material includes a core and a polymer conductive fiber layer, the polymer conductive fiber layer is coated on at least a portion of the surface of the core; the core includes a positive electrode active material, a solid electrolyte and a one-dimensional conductive fiber, the one-dimensional conductive fiber is distributed between the positive electrode active material and the solid electrolyte, so that the positive electrode active material, the solid electrolyte and the one-dimensional conductive fiber are closely connected, wherein the solid electrolyte and the one-dimensional conductive fiber are used to construct a fast ion transmission channel and an electronic conductive network, and improve the kinetic performance of the composite positive electrode material; the polymer conductive fiber layer includes polymer conductive fibers, at least part of the polymer conductive fibers and the one-dimensional conductive fibers are intertwined to form a conductive network, on the one hand, the polymer conductive fibers are intertwined with the first conductive fibers to form a conductive network connecting the core and the outer surface of the composite positive electrode material, and on the other hand, the strong binding force of the polymer conductive fibers intertwined with each other is used to improve the overall structural strength of the composite positive electrode material, inhibit the crushing of the composite positive electrode material particles, thereby improving the kinetic performance and structural strength of the composite positive electrode material of the present application. When the composite positive electrode material of the present application is applied to a solid-state battery, it can improve the capacity performance and cycle performance of the solid-state battery. When the above-mentioned solid-state battery is used in an energy storage device, the energy storage efficiency and service life of the energy storage device are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 A schematic diagram of the structure of particles of a composite positive electrode material according to an embodiment of the present application;

[0023] Figure 2 This is a schematic diagram of the structure of a solid-state electrode sheet according to an embodiment of the present application;

[0024] Figure 3 A schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application;

[0025] Figure 4 A schematic diagram of the structure of a commercial energy storage system according to an implementation scheme of the present application.

[0026] Explanation of the figure numbers: 1-energy storage device, 2-electric energy conversion device, 3-first user load, 4-second user load, 10-core, 11-positive electrode active material, 12-solid electrolyte, 13-one-dimensional conductive fiber, 20-polymer conductive fiber layer, 21-polymer conductive fiber, 30-current collector, 40-positive electrode material layer, 50-solid electrolyte layer, 400-commercial energy storage system, 410-high voltage cable, 420-first electric energy conversion device, 430-second electric energy conversion device. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0028] In the present application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings. These terms are mainly used to better describe the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation.

[0029] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.

[0030] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0031] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.

[0032] The present application provides a composite positive electrode material, such as Figure 1 As shown, the composite positive electrode material includes a core 10 and a polymer conductive fiber layer 20, and the polymer conductive fiber layer 20 is coated on at least a portion of the surface of the core 10, for example, the polymer conductive fiber layer is coated on the entire surface of the core to form a fully coated core-shell structure; or, the polymer conductive fiber layer is coated on a portion of the surface of the core to form a partially coated core-shell structure. The inner core 10 includes a granular positive electrode active material 11, a granular solid electrolyte 12 and a one-dimensional conductive fiber 13, wherein the one-dimensional conductive fiber 13 is distributed between the positive electrode active material 11 and the solid electrolyte 12 so that the positive electrode active material 11, the solid electrolyte 12 and the one-dimensional conductive fiber 13 are closely connected, wherein the solid electrolyte 12 and the one-dimensional conductive fiber 13 construct a fast ion transmission channel and an electronic conductive network, thereby improving the kinetic performance of the composite positive electrode material; the polymer conductive fiber layer 20 includes a polymer conductive fiber 21, wherein at least part of the polymer conductive fiber 21 and the one-dimensional conductive fiber 13 are mutually entangled to form a conductive network, on the one hand, the polymer conductive fiber 21 and the one-dimensional conductive fiber 13 are entangled to form a conductive network connecting the inner core and the outer surface of the composite positive electrode material, and on the other hand, the strong binding force of the polymer conductive fiber 21 entangled with each other is used to improve the overall structural strength of the composite positive electrode material, inhibit the crushing of the composite positive electrode material particles, thereby improving the kinetic performance and structural strength of the composite positive electrode material. When the composite positive electrode material of the present application is applied to a solid-state battery, the capacity performance and cycle performance of the solid-state battery can be improved. When the above-mentioned solid-state battery is used in an energy storage device, the energy storage efficiency and use of the energy storage device are improved.

[0033] In some embodiments of the present application, the mass percentage of the positive electrode active material in the core is a, 85% ≤ a ≤ 90%, the mass percentage of the solid electrolyte in the core is b, 5% ≤ b ≤ 10%, and the mass percentage of the one-dimensional conductive fiber in the core is c, 1% ≤ c ≤ 3%. For example, a is 85%, 87%, 88% or 90%, b is 5%, 7%, 8% or 10%, and c is 1%, 2% or 3%. By regulating the content of the positive electrode active material, the solid electrolyte, and the one-dimensional conductive fiber within the above range, it is beneficial to form a composite positive electrode material having the structure of the present application.

[0034] In some embodiments of the present application, the average length of the one-dimensional conductive fiber is L, 3μm≤L≤5μm. For example, L is 3μm, 3.5μm, 4μm, 4.5μm or 5μm. The inventors have found that increasing the average length of the one-dimensional conductive fiber is conducive to building a longer conductive network, but the longer the average length of the one-dimensional conductive fiber, the more difficult it is to stretch out, and it is easy to locally entangle and bend, weakening its conductive effect. In view of this, the present application selects a one-dimensional conductive fiber with the above average length, which is conducive to improving the conductive effect of the one-dimensional conductive fiber, thereby improving the kinetic properties of the composite positive electrode material.

[0035] In some embodiments of the present application, the thickness of the polymer conductive fiber layer is H, 2μm≤H≤5μm. For example, H is 2μm, 3μm, 4μm, 4.5μm or 5μm. The inventors have found that the thickness of the polymer conductive fiber layer should not be too thin or too thick. When it is too thin, the strength of the polymer conductive fiber layer decreases; when it is too thick, it will hinder the migration of lithium ions and reduce the capacity of the composite positive electrode material. In view of this, by regulating H within the above range, it is beneficial to form a polymer conductive fiber layer with strong binding force and high lithium ion mobility, which improves the overall structural strength of the composite positive electrode material while improving the capacity of the composite positive electrode material.

[0036] In some embodiments of the present application, the Dv50 of the composite positive electrode material is 8μm to 10μm. For example, the Dv50 of the composite positive electrode material is 8μm, 8.5μm, 9μm or 10μm. The inventors have found that when the Dv50 of the composite positive electrode material is too large, the migration distance of lithium ions becomes larger, which is not conducive to the performance of the capacity of the composite positive electrode material; when the Dv50 of the composite positive electrode material is too small, it is easy to cause the thickness of the polymer conductive fiber layer to be difficult to control, and it is easy to make the polymer conductive fiber layer too thick, which hinders the migration of lithium ions and also affects the performance of the capacity of the composite positive electrode material. By regulating the Dv50 of the composite positive electrode material within the above range, it is beneficial to improve the performance of the capacity of the composite positive electrode material.

[0037] In the present application, Dv50 means a particle size at which the volume accumulation is 50% from the smaller particle size side in a volume-based particle size distribution of particles.

[0038] In some embodiments of the present application, the one-dimensional conductive fibers extend outward from the inner core to the outer surface of the polymer conductive fiber layer. In this way, the one-dimensional conductive fibers can form a conductive path from the inner core to the outer surface together with the polymer conductive fiber layer, further improving the kinetic properties of the composite positive electrode material of the present application.

[0039] In some embodiments of the present application, the one-dimensional conductive fiber includes at least one of carbon conductive fiber and metal conductive fiber. Exemplarily, the carbon conductive fiber includes but is not limited to at least one of carbon fiber and graphite fiber; the metal conductive fiber includes but is not limited to at least one of copper-based conductive fiber, silver-based conductive fiber and nickel-based conductive fiber. The one-dimensional conductive fiber has high conductivity, which is conducive to improving the kinetics of the composite positive electrode material of the present application.

[0040] In some embodiments of the present application, the polymer in the polymer conductive fiber includes at least one of polyaniline, polypyrrole and polythiophene.

[0041] In some embodiments of the present application, the kernel further includes a binder, and the mass percentage of the binder in the kernel is d, 1%≤d≤3%. For example, d is 1%, 2% or 3%. By regulating the content of the binder within the above range, it is beneficial to make the positive electrode active material, the solid electrolyte and the one-dimensional conductive fiber adhere together better, improve the structural stability of the kernel, and further improve the structural stability of the composite positive electrode material. The binder of the present application includes but is not limited to polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), etc.

[0042] The positive electrode active material of the present application can be a nanoscale material, which is beneficial to shorten the Li + Migration path to improve Li + diffusion capacity; the solid electrolyte of the present application can be a nanoscale material, which is beneficial to improve the lithium ion transmission rate.

[0043] The present application has no particular restrictions on the preparation method of the composite positive electrode material, as long as the purpose of the present application can be achieved. Exemplarily, it can be prepared by the following steps:

[0044] Step A, mixing a positive electrode active material, a solid electrolyte, a one-dimensional conductive fiber and a binder according to a designed content ratio to obtain a mixture, adding a solvent to the mixture, and mixing evenly to obtain a first slurry;

[0045] Step B, spray drying the first slurry to form a granular core precursor;

[0046] Step C, mixing the core precursor and the monomer of the polymer, then adding water, stirring evenly to form a dispersion, then dropping a metal salt solution into the dispersion, reacting at a temperature of 4°C to 6°C for 10h to 20h to obtain a composite positive electrode material.

[0047] In step A, the solvent can be selected from N-methylpyrrolidone (NMP) or other solvents, and there is no special limitation in the present application; the binder can be selected from PVDF or other binders, and there is no special limitation in the present application; the solid content of the first slurry is 50% to 60%.

[0048] In step B, the pump speed of spray drying is 8 mL / min to 12 mL / min, and the drying temperature is 180° C. to 220° C., which is conducive to forming a granular core precursor, thereby facilitating the formation of a structured composite positive electrode material of the present application.

[0049] In step C, the mass ratio of the core precursor to the monomer of the polymer is 1:(0.2~0.7); the monomer of the polymer is selected from at least one of pyrrole, thiophene and acrylonitrile; water is pure water or deionized water; during stirring, ultrasonic dispersion and magnetic stirring can be combined to facilitate uniform dispersion of the monomers of the core precursor and the polymer; the molar concentration of the metal salt in the metal salt solution is 0.5mol / L~1mol / L; the molar ratio of the metal salt to the monomer of the polymer is 1:(0.8~1.2), the metal salt can be selected from FeCl3, and can also be selected from other metal salts, and there is no special restriction in this application; when the metal salt solution is added dropwise, the temperature of the solution is 4°C~6°C, so that the reaction can be fully carried out to form polymer conductive fibers, and the polymer conductive fibers can be more evenly coated on the particle surface of the core precursor, which is conducive to the formation of a composite positive electrode material with excellent conductivity and uniform coating.

[0050] After the reaction is completed, the reaction product can be washed and filtered with anhydrous ethanol and deionized water in turn until the washing liquid is clear and colorless, and then the product is placed in a freeze dryer and cooled and dried at -55°C to -45°C to obtain a purified composite positive electrode material.

[0051] In the process of preparing the composite positive electrode material of the present application, the raw materials used (such as positive electrode active materials, solid electrolytes, one-dimensional conductive fibers and binders, etc.) can be obtained through commercial channels. The present application has no special restrictions as long as the purpose of the present application can be achieved.

[0052] The present application has no particular restrictions on the type of positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material includes but is not limited to lithium iron phosphate, lithium iron manganese phosphate or ternary materials. Exemplarily, specifically, the positive electrode active material includes but is not limited to LiFePO4, LiMn 0.6 Fe 0.4 PO4 / C、LiNi 0.6 Co 0.2 Mn 0.2 O2, etc.

[0053] The present application has no particular restrictions on the type of solid electrolyte, as long as the purpose of the present application can be achieved. For example, the solid electrolyte includes but is not limited to at least one of a polymer solid electrolyte, an oxide solid electrolyte, and a sulfide solid electrolyte. Exemplarily, specifically, the solid electrolyte includes Li 1.3 Al0.3 Ti 1.7 (PO4)3, Li7La3Zr2O 12 , Li2S-P2S5 and Li2S-SiS2-P2S5-LiI.

[0054] The Dv50 of the composite positive electrode material generally increases with the increase of the particle size of the core precursor. Furthermore, the particle size of the core precursor generally increases with the increase of the pump speed (feed rate) during the spray drying process, and decreases with the increase of the drying temperature. Based on this, the present application can regulate the Dv50 of the composite positive electrode material by regulating the pump speed and the drying temperature.

[0055] The thickness of the polymer conductive fiber layer generally increases with the increase in the monomer specific gravity of the polymer in the dispersion. Based on this, the present application can control the thickness of the polymer conductive fiber layer by adjusting the mass ratio of the core precursor to the monomer of the polymer in the dispersion.

[0056] The present application also provides a solid electrode sheet, such as Figure 2 As shown, it includes a current collector 30, at least one side of the current collector 30 has a positive electrode material layer 40, and the positive electrode material layer 40 includes the composite positive electrode material described in any of the above embodiments. The present application has no particular limitation on the thickness of the positive electrode material layer 40, as long as the purpose of the present application can be achieved, for example, the thickness of the positive electrode material layer 40 is 10 μm to 60 μm.

[0057] In some embodiments of the present application, Figure 2 As shown, the solid electrode sheet further includes a solid electrolyte layer 50, which is located on the side of the positive electrode material layer 40 away from the current collector 30. The present application has no particular limitation on the thickness of the solid electrolyte layer, as long as the purpose of the present application can be achieved, for example, the thickness of the solid electrolyte layer is 5 μm to 15 μm.

[0058] In the present application, the material of the current collector is generally not limited, as long as the positive electrode current collector has good conductivity and does not react with other substances in the solid-state battery. For example, the material of the current collector includes but is not limited to aluminum, stainless steel, etc. The thickness of the current collector can be controlled within the range of 2 μm to 1000 μm.

[0059] In the present application, the negative electrode plate may be made of at least one of a pure lithium plate, a lithium metal composite oxide plate and a lithium alloy plate.

[0060] The present application also provides a solid-state battery, comprising the solid-state electrode sheet described in any of the above embodiments.

[0061] The battery of the present application also includes a shell, and the present application has no particular restrictions on the shell, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. For example, the shell may include a steel shell, an aluminum alloy shell or an aluminum-plastic film.

[0062] The present application also provides an energy storage device, comprising a housing and at least one solid-state battery in any of the above embodiments, wherein the solid-state battery is contained in the housing. The energy storage device having the solid-state battery has excellent performance, which is beneficial to the use of the energy storage device. By containing the solid-state battery in the housing, the fixation and protection of the solid-state battery can be increased, thereby improving the service life of the energy storage device. It is understandable that the energy storage device may have one or more solid-state batteries, and when the energy storage device contains multiple solid-state batteries, the multiple solid-state batteries may be connected in at least one of parallel and series connection.

[0063] The present application also provides an electrical device, including the energy storage device in the above-mentioned implementation scheme, which is conducive to improving the product competitiveness and performance of the electrical equipment. In an optional implementation scheme, the electrical equipment includes an electrical equipment body, and the energy storage device is used to supply power to the electrical equipment body. In an optional implementation scheme, the electrical equipment body includes an equipment positive electrode and an equipment negative electrode, and the positive electrode plate of the solid-state battery in the energy storage device is used to electrically connect to the equipment positive electrode of the electrical equipment body, and the negative electrode plate of the solid-state battery in the energy storage device is used to electrically connect to the equipment negative electrode of the electrical equipment body to supply power to the electrical equipment.

[0064] The electrical equipment of the present application may include but is not limited to: containers, battery vehicles, electric vehicles, ships, spacecraft, electric toys and electric tools, etc., wherein spacecrafts include airplanes, rockets, space shuttles and spacecrafts, etc., electric toys include fixed or mobile electric toys, such as electric car toys, electric ship toys and electric airplane toys, etc., and electric tools include metal cutting power tools, grinding power tools, assembly power tools and railway power tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers.

[0065] See also Figure 3 , Figure 3 This is a schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application, and the present application Figure 3 The implementation plan is described using a household energy storage scenario in user-side energy storage as an example, but the energy storage device of the present application is not limited to the household energy storage scenario.

[0066] The present application provides a household energy storage system, which includes an energy conversion device 2 (photovoltaic panel), a first user load 3 (street lamp), a second user load 4 (such as air conditioner and other household appliances), and an energy storage device 1. The energy storage device 1 is a small energy storage box that can be mounted on an outdoor wall by wall hanging. Specifically, the photovoltaic panel can convert solar energy into electrical energy during the period of low electricity prices. The energy storage device 1 is used to store the electrical energy and supply it to street lamps and household appliances for use during the peak electricity prices, or to supply power when the power grid is out of power / power outage.

[0067] See also Figure 4 , Figure 4 A schematic diagram of a commercial energy storage system 400 according to an embodiment of the present application. Figure 4 The implementation plan is described using the shared energy storage scenario on the generation / distribution side as an example, and the energy storage device 1 of the present application is not limited to the energy storage scenario on the generation / distribution side.

[0068] The present application provides a commercial energy storage system 400, which includes: a high-voltage cable 410, a first electric energy conversion device 420, a second electric energy conversion device 430 and an energy storage device 1 provided in the present application. In the case of power generation, the first electric energy conversion device 420 and the second electric energy conversion device 430 are used to convert other forms of energy into electric energy, which are connected to the high-voltage cable 410 and supplied to the power distribution network for use. When the power load is low and the first electric energy conversion device 420 and the second electric energy conversion device 430 generate excess power, the excess power is stored in the energy storage device 1, thereby reducing the wind and solar power abandonment rates and improving the problem of new energy power generation and consumption. When the power load is high, the power grid issues an instruction to transmit the power stored in the energy storage device 1 in conjunction with the high-voltage cable 410 in a grid-connected mode to the power consumption side, thereby providing peak load regulation, frequency regulation, standby and other services for the power grid operation, giving full play to the peak load regulation of the power grid, promoting peak load shaving and valley filling of the power grid, and alleviating the power supply pressure of the power grid.

[0069] Optionally, the first electric energy conversion device 420 and the second electric energy conversion device 430 can convert at least one of solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.

[0070] The number of energy storage devices 1 can be multiple, and multiple energy storage devices 1 are connected in series or in parallel. Multiple energy storage devices 1 are supported and electrically connected by isolation plates (not shown). In this embodiment, "multiple" refers to two or more. An energy storage box can also be provided outside the energy storage device 1 to accommodate the energy storage device 1.

[0071] Optionally, the energy storage device 1 may include but is not limited to a battery module, a battery pack, a battery system, etc. Among them, the battery module may be a battery module formed by connecting multiple batteries of the present application in series / parallel, the battery pack may include multiple solid-state batteries of the present application, and the battery system may be a charging and discharging system including the solid-state battery or battery pack of the present application.

[0072] The actual application form of the energy storage device 1 provided in the embodiment of the present application may be, but is not limited to, the listed products, and may also be other application forms. The embodiment of the present application does not strictly limit the application form of the energy storage device 1. The embodiment of the present application only takes the energy storage device 1 as a multi-core battery as an example for explanation. When the energy storage device 1 includes a single cell, the single cell may be at least one of a cylindrical battery, a square battery, and the like.

[0073] Example

[0074] Hereinafter, the embodiments of the present application will be described in more detail with reference to preparation examples, examples and comparative examples. Various tests and evaluations were performed according to the following methods.

[0075] Example 1

[0076] <Preparation of composite positive electrode material>

[0077] According to the mass ratio of 85:10:2:3, lithium iron phosphate (LiFePO4, Dv50 is 0.75 μm) and solid electrolyte Li 1.3 Al 0.3 Ti 1.7(PO4)3 (Dv50 is 0.6μm), carbon conductive fiber (Tianjin Jinglin New Material Technology Co., Ltd., model: ECC-F) (i.e. one-dimensional conductive fiber) and binder PVDF, mix the above raw materials and add NMP, stir continuously and mix evenly to form a first slurry with a solid content of 60%; spray dry the first slurry, the pump speed of the spray drying is 9mL / min, the drying temperature is 200℃, to form a granular core precursor; mix the core precursor with pyrrole monomer (i.e. monomer of the polymer) in a mass ratio of 1:0.3, then add deionized water, and then use ultrasonic dispersion and magnetic stirring to prepare a dispersion, and then continue to stir the dispersion at 10℃, and then add FeCl3 solution drop by drop into the dispersion according to the molar ratio of pyrrole monomer to FeCl3 in the dispersion of 1:1, and react at a temperature of 5℃ for 10h to allow the solution to react fully. After the reaction is completed, the reaction product is washed and filtered with anhydrous ethanol and deionized water until the washing liquid is clear and colorless, and then the product is placed in a freeze dryer and cooled and dried at -50°C to obtain a purified composite positive electrode material. The average length L of the one-dimensional conductive fiber and the Dv50 of the composite positive electrode material are shown in Table 1. The thickness of the polymer conductive fiber layer on the outer surface of the composite positive electrode material is about 2 μm as measured by transmission electron microscopy (TEM).

[0078] <Preparation of positive electrode material layer>

[0079] The prepared composite positive electrode material and solid electrolyte Li were weighed according to the mass ratio of 90:5:2:3. 1.3 Al 0.3 Ti 1.7 (PO4)3, graphene (as a conductive agent), and PVDF (as a binder) are mixed evenly in a stirring tank, and solvent NMP is added and mixed evenly to form a second slurry with a solid content of 65%. The second slurry is coated on an aluminum foil with a thickness of 15 μm, and vacuum dried in a vacuum drying oven at 150°C for 15 hours to form a positive electrode material layer with a thickness of 30 μm.

[0080] <Preparation of solid electrode sheet>

[0081] According to the mass ratio of 95:5, the solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO4)3 and PVDF (as a binder) are mixed evenly in a stirring tank, and the solvent NMP is added and mixed evenly to form a third slurry with a solid content of 60%. The third slurry is coated on the surface of the positive electrode material layer, and dried in a vacuum drying oven at 150°C to form a solid electrolyte layer with a thickness of 5μm, thereby forming a solid electrode sheet.

[0082] <Preparation of solid-state batteries>

[0083] The positive electrode shell, solid electrode sheet, negative electrode lithium sheet, stainless steel gasket, spring and negative electrode shell are assembled in the glove box in the order, and then placed on a sealing machine to encapsulate a CR2032 button battery.

[0084] Embodiment 2 to Embodiment 8

[0085] Except that in <Preparation of Composite Positive Electrode Material>, the contents of positive electrode active material, solid electrolyte, one-dimensional conductive fiber and binder are adjusted according to Table 1, the rest is the same as Example 1.

[0086] Embodiment 9 to Embodiment 12

[0087] Except that the relevant preparation parameters in <Preparation of composite positive electrode material> are adjusted according to Table 2, the rest is the same as Example 1.

[0088] Example 13 to Example 17

[0089] The method is the same as Example 1 except that in <Preparation of Composite Positive Electrode Material>, the thickness of the polymer conductive fiber layer is adjusted according to Table 2 by adjusting the mass ratio of the core precursor to the pyrrole monomer, that is, by adjusting the monomer specific gravity of the polymer in the dispersion.

[0090] Example 18 to Example 21

[0091] Except that in <Preparation of Composite Positive Electrode Material>, the Dv50 of the composite positive electrode material was adjusted according to Table 2 by adjusting the pump speed during the spray drying process, the rest was the same as Example 1.

[0092] Example 22 to Example 23

[0093] Except that the type of positive electrode active material is adjusted according to Table 2 in <Preparation of Composite Positive Electrode Material>, the rest is the same as Example 1.

[0094] Comparative Example 1

[0095] Except that the composite positive electrode material of the present application is not used in the preparation of the positive electrode material layer, the rest is the same as in Example 1. The preparation process of the positive electrode material layer is as follows:

[0096] According to the mass ratio of 90:5:2:3, lithium iron phosphate (LiFePO4) and solid electrolyte Li 1.3 Al 0.3 Ti 1.7(PO4)3, graphene (acting as a conductive agent) and binder PVDF, mix the raw materials and add NMP, stir continuously and mix evenly to form a fourth slurry with a solid content of 65%, coat the fourth slurry on an aluminum foil with a thickness of 15 μm, and vacuum dry it in a vacuum drying oven at 150°C for 15 hours to form a positive electrode material layer with a thickness of 30 μm.

[0097] Comparative Example 2 to Comparative Example 3

[0098] Except that the type of the positive electrode active material was adjusted according to Table 2 in <Preparation of Positive Electrode Material Layer>, the rest was the same as Comparative Example 1.

[0099] Table 1: Preparation parameters of Examples 1 to 8 and Comparative Example 1

[0100] a(wt%) b(wt%) c(wt%) d(wt%) Example 1 85 10 2 3 Example 2 86 9 2 3 Example 3 87 8 2 3 Example 4 88 7 2 3 Example 5 89 6 2 3 Example 6 90 5 2 3 Example 7 91 4 2 3 Example 8 84 11 2 3 Comparative Example 1 / / / /

[0101] Note: In Table 1, “ / ” indicates that there is no relevant preparation parameter.

[0102] Table 2: Preparation parameters of Example 1, Example 9 to Example 23, Comparative Example 2 to Comparative Example 3

[0103]

[0104]

[0105] Note: In Table 2, “ / ” indicates that there is no relevant preparation parameter.

[0106] Test methods and equipment:

[0107] Particle size distribution test:

[0108] The particle size distribution of the composite positive electrode material was measured using a laser diffraction particle size distribution measuring instrument (Malvern Mastersizer 3000) according to the particle size distribution laser diffraction method GB / T19077-2016, thereby measuring the Dv50 of the composite positive electrode material.

[0109] Thickness test of polymer conductive fiber layer:

[0110] The polymer conductive fiber layer was observed by transmission electron microscopy (TEM), and the thickness of the polymer conductive fiber layer was measured.

[0111] Rate discharge capacity test:

[0112] At 25°C, the lithium solid-state batteries prepared in each embodiment and comparative example were charged to voltage V1 at 0.1 times (C) using a Nebula charge and discharge test system (BAT-NEEFLCT-05300-V010), and then discharged to voltage V2 at 0.1C times, and the discharge capacity at this time was recorded as 0.1C discharge capacity. Among them, the voltage V1 corresponding to the lithium iron phosphate material is 3.75V, and the corresponding voltage V2 is 2.5V; the voltage V1 corresponding to the lithium iron manganese phosphate material is 4.3V, and the corresponding voltage V2 is 2.5V; the voltage V1 corresponding to the ternary material is 4.3V, and the corresponding voltage V2 is 2.8V.

[0113] Cycle performance test:

[0114] At 25°C, the lithium solid-state batteries prepared in the embodiments and comparative examples were charged to the above voltage V1 at 1C using the Nebula charge and discharge test system (BAT-NEEFLCT-05300-V010), and then discharged to the above voltage V2 at a rate of 1C to calculate the capacity retention rate after the cycle. The capacity retention rate calculation formula is: 200 cycles (cls) cycle capacity retention rate = (discharge capacity after the 200th cycle / discharge capacity of the first cycle) × 100%.

[0115] Table 3: Performance data of various embodiments and comparative examples

[0116] 0.1C discharge capacity (mAh / g) Capacity retention rate (%) Example 1 143.5 91.5 Example 2 143.8 91.7 Example 3 144.2 92.0 Example 4 144.6 92.2 Example 5 145.0 92.5 Example 6 143.6 91.5 Example 7 142.7 90.7 Example 8 142.5 90.5 Example 9 144.0 92.0 Example 10 143.7 91.4 Embodiment 11 142.8 90.7 Example 12 143.0 90.3 Embodiment 13 143.7 92.0 Embodiment 14 144.5 92.5 Embodiment 15 143.5 92.1 Example 16 142.7 90.5 Embodiment 17 142.6 90.1 Embodiment 18 143.6 91.5 Embodiment 19 144.4 92.5 Embodiment 20 140.1 90.5 Embodiment 21 138.0 89.2 Embodiment 22 142.4 91.0 Embodiment 23 165.6 90.6 Comparative Example 1 135.0 88.7 Comparative Example 2 130.1 84.5 Comparative Example 3 161.0 82.6

[0117] It can be seen from Example 1 and Comparative Example 1, Example 22 and Comparative Example 2, and Example 23 and Comparative Example 3 that since the 0.1C discharge capacity and the cycle capacity retention rate after 200 cycles of Comparative Example 1 are both low, this may be because the solid electrode sheet of Comparative Example 1 does not have the composite positive electrode material structure of the present application, resulting in poor kinetics and low capacity utilization of its lithium iron phosphate positive electrode material; the 0.1C discharge capacity and the cycle capacity retention rate after 200 cycles of Comparative Example 2 are also low, which may be because the solid electrode sheet of Comparative Example 2 also does not have the composite positive electrode material structure of the present application, resulting in poor kinetics and low capacity utilization of its lithium iron manganese phosphate positive electrode material; although the 0.1C discharge capacity of Comparative Example 3 is relatively high, the cycle capacity retention rate after 200 cycles is low, which may be because although the ternary material of Comparative Example 3 can increase the capacity, the ternary material does not have the structure of the composite positive electrode material of the present application, resulting in poor ternary material kinetics. The 0.1C discharge capacity and the cycle capacity retention rate after 200 cycles of the lithium solid-state batteries in each embodiment of the present application are improved, indicating that when the composite positive electrode material of the present application is applied to lithium solid-state batteries, it can improve the capacity performance and cycle performance of lithium solid-state batteries.

[0118] The contents of the positive electrode active material, solid electrolyte, one-dimensional conductive fiber and other components in the core of the composite positive electrode material usually also affect the performance of the composite positive electrode material, and thus affect the performance of the lithium solid-state battery. It can be seen from Examples 1 to 8 that, on the basis of the composite positive electrode material having the structure of the present application, by regulating the above parameters within the scope of the present application, it is beneficial to obtain a lithium solid-state battery with excellent capacity performance and cycle performance.

[0119] The average length of the one-dimensional conductive fiber, the thickness of the polymer conductive fiber layer, the Dv50 of the composite positive electrode material, and the type of positive electrode active material in the core usually also affect the performance of the composite positive electrode material, and then affect the performance of the lithium solid-state battery. It can be seen from Examples 1 and 9 to 23 that, on the basis of the composite positive electrode material having the structure of the present application, by regulating the above parameters within the scope of the present application, it is beneficial to obtain a lithium solid-state battery with excellent capacity performance and cycle performance.

[0120] The above is a detailed introduction to a composite positive electrode material, a solid-state electrode sheet, a solid-state battery and an energy storage device disclosed in the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions and core inventions of the embodiments of the present application. At the same time, for general technicians in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A composite positive electrode material, characterized in that: It comprises an inner core and a polymer conductive fiber layer, wherein the polymer conductive fiber layer is coated on at least a portion of the surface of the inner core; The inner core includes a positive electrode active material, a solid electrolyte and a one-dimensional conductive fiber, wherein the one-dimensional conductive fiber is distributed between the positive electrode active material and the solid electrolyte; The polymer conductive fiber layer includes polymer conductive fibers, and at least a portion of the polymer conductive fibers are entangled with the one-dimensional conductive fibers to form a conductive network.

2. The composite positive electrode material according to claim 1, characterized in that The mass percentage of the positive electrode active material in the core is a, 85%≤a≤90%, the mass percentage of the solid electrolyte in the core is b, 5%≤b≤10%, and the mass percentage of the one-dimensional conductive fiber in the core is c, 1%≤c≤3%.

3. The composite positive electrode material according to claim 1, characterized in that: The average length of the one-dimensional conductive fibers is L, 3 μm≤L≤5 μm.

4. The composite positive electrode material according to claim 1, characterized in that The thickness of the polymer conductive fiber layer is H, 2 μm≤H≤5 μm.

5. The composite positive electrode material according to claim 1, characterized in that: The Dv50 of the composite positive electrode material is 8 μm to 10 μm.

6. The composite positive electrode material according to claim 1, characterized in that: The one-dimensional conductive fibers extend outward from the inner core to the outer surface of the polymer conductive fiber layer.

7. The composite positive electrode material according to claim 1, characterized in that: The one-dimensional conductive fibers include at least one of carbon conductive fibers and metal conductive fibers.

8. The composite positive electrode material according to claim 1, characterized in that: The polymer in the polymer conductive fiber includes at least one of polyaniline, polypyrrole and polythiophene.

9. The composite positive electrode material according to claim 2, characterized in that: The inner core further comprises a binder, and the mass percentage of the binder in the inner core is d, 1%≤d≤3%.

10. A solid electrode sheet, characterized in that: It comprises a current collector, at least one side of which has a positive electrode material layer, and the positive electrode material layer comprises the composite positive electrode material according to any one of claims 1 to 9.

11. The solid electrode sheet according to claim 10, characterized in that: The solid electrode sheet further comprises a solid electrolyte layer, and the solid electrolyte layer is located on a side of the positive electrode material layer away from the current collector.

12. A solid-state battery, characterized in that: Comprising the solid electrode sheet according to claim 10 or 11.

13. An energy storage device, characterized in that: It comprises a casing and at least one solid-state battery according to claim 12, wherein the solid-state battery is accommodated in the casing.

14. An electrical device, characterized in that: It includes the energy storage device as described in claim 13, and the energy storage device supplies power to the electrical equipment.